Limitaciones en el Código Orgánico de la Niñez y Adolescencia de los alimentos prioritarios y superiores de las personas con discapacidad - Celi Alvarez, Maira Verónica (2017)
Due to different circumstances of genetic order in some cases and in others as a result of involuntary situations, there are people who have been diminished his physical, intellectual, mental or sensory abilities, considered as persons with disabilities, who by their vulnerability, are made creditors priority, preferential and specialized by the State and society in general protection, because of this I synthesized my study this group focus on maintenance that should receive to cover their basic needs, through the whole existing provisions in the objective law, binding on constitutional rights and alimony as a necessity for harmonious development of good living. The importance lies as the reference group, according to a principle interest is higher, in addition constitutionally established that the State, society and family as a priority, promote the comprehensive development in all aspects. For the above my work focuses on the need to regulate alimony as a priority and above, people with disabilities, and thus to improve their quality of life.